2009
DOI: 10.7127/rbai.v3n100012
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento da cana-de-açúcar com e sem irrigação complementar sob diferentes níveis de adubação de cobertura nitrogenada e potássica

Abstract: RESUMO:Realizou-se esta pesquisa para determinar o efeito de diferentes níveis de adubação de cobertura, sobre os parâmetros de crescimento da terceira folha de cana (variedade SP-791011) cultivada com e sem irrigação complementar, em área da Destilaria Miriri, município de Capim, PB. O arranjo experimental foi um fatorial 2 x 4 (com e sem irrigação, e quatro doses de adubação de cobertura de N e K 2 O) com três repetições. A lâmina de irrigação usada, 27,5 mm, foi aplicada em intervalos de irrigação de 12 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Souza et al (2015) found a significant effect of irrigation on plants' growth in height and on culm phytomass of sugarcane (variety SP 79-1011). Silva et al (2009) found in this variety that the sugarcane growth parameters values, related to the number of culms, culm length, culm diameter, number of internodes and culm weight, responded significantly to irrigation.…”
Section: Resultsmentioning
confidence: 72%
“…Souza et al (2015) found a significant effect of irrigation on plants' growth in height and on culm phytomass of sugarcane (variety SP 79-1011). Silva et al (2009) found in this variety that the sugarcane growth parameters values, related to the number of culms, culm length, culm diameter, number of internodes and culm weight, responded significantly to irrigation.…”
Section: Resultsmentioning
confidence: 72%
“…According to Silva et al [2], for maximum yield, sugarcane needs adequate moisture, directly proportional to the transpired water, throughout its vegetal growth. Thus, irrigation becomes indispensable for greater productivity.…”
Section: Introductionmentioning
confidence: 99%